Spatholobus suberectus Exhibits Antidiabetic Activity In Vitro and In Vivo through Activation of AKT-AMPK Pathway. (18th May 2017) - Zhao, Peijun; Alam, Md Badrul; Lee, Seok-hyun; Kim, Young-Jun; Lee, Seul; An, Hongyan; Choi, Hee-Jeong; Son, Hyeong-U; Park, Chul-Hong; Kim, Hyo-Hyun; Lee, Sang-Han
Abstract : Glucose deposition in peripheral tissue is an important parameter for the treatment of type 2 diabetes mellitus. The aim of this study was to investigate the effects of Spatholobus suberectus (Ss) on glucose disposal in skeletal muscle cells and additionally explore its in vivo antidiabetic potential. Treatment of ethanolic extract of S. suberectus (EeSs) significantly enhanced the glucose uptake, mediated through the enhanced expression of GLUT4 in skeletal muscle via the stimulation of AKT and AMPK pathways in C2C12 cells. Moreover, EeSs have potential inhibitory action on α -glucosidase activity and significantly lowered the postprandial blood glucose levels in STZ-induced diabetic mice, associated with increased expression of GLUT4 and AKT and/or AMPK-mediated signaling cascade in skeletal muscle. Furthermore, administration of EeSs significantly boosted up the antioxidant enzyme expression and also mitigated the gluconeogenesis enzyme such as PEPCK and G-6-Pase enzyme expression in liver tissue of STZ-induced diabetic mice model. Collectively, these findings suggest that EeSs have a high potentiality to mitigate diabetic symptoms through stimulating glucose uptake in peripheral tissue via the activation of AKT and AMPK signaling cascade and augmenting antioxidant potentiality as well as blocking the gluconeogenesis process in diabetic mice.